2017
DOI: 10.24095/hpcdp.37.7.02
|View full text |Cite
|
Sign up to set email alerts
|

Estimating multimorbidity prevalence with the Canadian Chronic Disease Surveillance System

Abstract: Introduction The Public Health Agency of Canada’s Canadian Chronic Disease Surveillance System (CCDSS) uses a validated, standardized methodology to estimate prevalence of individual chronic diseases, such as diabetes. Expansion of the CCDSS for surveillance of multimorbidity, the co-occurrence of two or more chronic diseases, could better inform health promotion and disease prevention. The objective of this study was to assess the feasibility of using the CCDSS to estimate multimorbidity prevalence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 30 publications
(42 reference statements)
4
66
4
Order By: Relevance
“…Previous analyses showing lower but increasing chronic disease prevalence in northern Canada were not adjusted for known risk factors beyond age and sex [18,21,24]. Our results contradict predictions of rising chronic disease among northern populations made in previous studies; however, we did not use a longitudinal design so could not test for trend.…”
Section: Strengths and Limitationscontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous analyses showing lower but increasing chronic disease prevalence in northern Canada were not adjusted for known risk factors beyond age and sex [18,21,24]. Our results contradict predictions of rising chronic disease among northern populations made in previous studies; however, we did not use a longitudinal design so could not test for trend.…”
Section: Strengths and Limitationscontrasting
confidence: 99%
“…Feely et al used the Canadian Chronic Disease Surveillance System (populated by administrative hospital discharge and physician claims data) to analyze multimorbidity across Canadian provinces and territories. They found slightly higher age-standardized rates of three or more chronic conditions in the Yukon and Nunavut compared to Canada overall with higher than average increases in all three territories between 2001/02 and 2011/12 [24]. However, their estimates are were also not adjusted for risk factors such as smoking, diet, physical activity, or socioeconomic status [24].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…protocol registration: PROSPERO-CRD42014014489 needs, are at higher risk for adverse health outcomes and are admitted to hospital more frequently, 10 yet only 55% receive appropriate care. 7,8 In response, different interventions for managing chronic disease have been created (i.e., those that facilitate ongoing, proactive and preventive support for optimal management of disease). These strategies have potential to improve care for older adults, 11,12 but are not usually developed for older adults nor sustainable, and focus only on a single disease.…”
mentioning
confidence: 99%
“…The GBD Study does not model subnational (provincial/ territorial or regional) or other important subpopulation (e.g., Indigenous people, people living with low income) estimates for Canada, which may be important, given that previous research has identified variability in disease estimates across Canada. 24,25 These limitations may be addressed in future iterations of the GBD Study. The 2016 estimates provided here do not incorporate the most current vital statistics because of the time lag in releasing data, which means that our results may not reflect any recent and important changes such as the opioid epidemic.…”
mentioning
confidence: 99%